Transient Modulation of Working Memory Performance and Event-Related Potentials by Transcranial Static Magnetic Field Stimulation over the Dorsolateral Prefrontal Cortex - Chen, Xiaoxiao (Brain Sci, 2021)
Transcranial static magnetic field stimulation (tSMS) can modulate human cortical excitability and behavior. To better understand the neuromodulatory effect of tSMS, this study investigates whether tSMS applied over the left dorsolateral prefrontal cortex (DLPFC) modulates working memory (WM) performance and its associated event-related potentials (ERPs). Thirteen healthy participants received tSMS or sham stimulation over the left DLPFC for 26 min on different days. The participants performed a 2-back version of the n-back task before, during (20 min after the start of stimulation), immediately after, and 15 min after the stimulation. We examine reaction time for correct responses, d-prime reflecting WM performance, and the N2 and P3 components of ERPs. Our results show that there was no effect of tSMS on reaction time. The d-prime was reduced, and the N2 latency was prolonged immediately after tSMS. These findings indicate that tSMS over the left DLPFC affects WM performance and its associated electrophysiological signals, which can be considered an important step toward a greater understanding of tSMS and its use in studies of higher-order cognitive processes.